1998
DOI: 10.1046/j.1365-2362.1998.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies directed against phospholipids or human β2‐glycoprotein 1 in HIV‐seropositive patients: relationship with endothelial activation and antimalonic dialdehyde antibodies

Abstract: BackgroundWe investigated the possible role of antiphospholipid (APA) and anti-human 2 -glycoprotein I (b 2 -GPI) antibodies (Ab) in thrombosis and atherosclerosis in human immunodeficiency (HIV)-positive patients, in whom they seem to be more frequent. MethodsWe measured APA and anti-b 2 -GPI Ab in 58 HIV-positive patients together with markers of disease progression, circulating b 2 -GPI, plasma lipids, biological markers of endothelial activation and integrity (plasma thrombomodulin, von Willebrand factor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 47 publications
2
26
1
2
Order By: Relevance
“…HLA molecules, CD95, phospholipids, human ␤2 glycoprotein-1, neutrophil cytoplasmic antigens, are frequently observed in untreated HIV-infected individuals [3][4][5][6][7][8][9]. Disturbances in mechanisms of self-recognition were shown to parallel the progression of HIV-1 infection [3,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HLA molecules, CD95, phospholipids, human ␤2 glycoprotein-1, neutrophil cytoplasmic antigens, are frequently observed in untreated HIV-infected individuals [3][4][5][6][7][8][9]. Disturbances in mechanisms of self-recognition were shown to parallel the progression of HIV-1 infection [3,23].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of the B cell compartment include polyclonal B cell activation [1,2] and high levels of self-reactive antibodies in serum [3][4][5][6][7][8][9]. Natural antibodies of the IgM, IgG, and IgA isotype that are reactive with a stages of HIV infection using quantitative immunoblotting followed by multiparametric statistical analysis of the data.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that aPL can be induced in patients infected with many bacteria, other microorganisms (35)(36)(37)(38)(39)(40)(41)(42)(43)(44), and viruses, including CMV (45), varicella zoster virus (46), human immunodeficiency virus (47), hepatitis C (48), and Epstein-Barr virus (49). In addition, transient LAC activity in patients with Epstein-Barr virus infections has been reported (49).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the presence of these antibodies was not associated with clinical manifestations of APS, and the antibodies did not require 2 GPI for binding to CL. Recently, the belief that infection-associated aPl are 2 GPI-independent, do not bind to 2 GPI in the absence of phospholipids, and are not associated with thrombosis or other clinical complications of APS has been challenged in a significant number of reports [44][45][46][47][48][49][50][51][52][53]. In one study, aCL present in leprosy patients were shown to be heterogenous with respect to their 2 GPI requirement: in 10 of 31 leprosy sera, the aCL were 2 GPI dependent, and 21 of 31 did not require 2 GPI for binding to CL.…”
Section: Discussionmentioning
confidence: 99%